Efficiency investigation of mitigation effect of isolation piles on tunneling-induced ground settlements - ZHENG Zhenji; CAO Liqiang; SU Dong; CHEN Xiangsheng (Shenzhen Daxue xuebao. Ligong ban)
In order to study the control efficiency of isolation pile on the settlement of the surface and deep soil, we analyze the implementation method of simulated isolation pile in Plaxis2d, and establish the finite element model of the tunnel and isolation pile interaction to study the effects of the pile length, pile diameter, buried depth of pile top, pile horizontal position and tunnel buried depth on the control effectiveness. The results show that the control effectiveness of the isolation pile on the ground surface and deep soil strata subsidence is different. Under the uniform radial contraction mode of the tunnel, the pile length has the most obvious impact on the ground surface. In practical projects, it should be at least one radiu at the bottom of the deep tunnel to ensure the control effect on surface subsidence. The closer the isolation pile is set to the tunnel, the better the control efficiency is, especially to the settlement of deep soil. Within 0.6 ~ 1.4 m pile diameter changes on the isolation is of little influence on the pile settlement control effectiveness. The control efficiency of buried isolation pile on ground settlement is not much different from that of non-buried one, but the control efficiency of deep soil settlement in the ground is obviously better than that of the non-buried isolation pile. For the same isolation pile, the deeper the tunnel is buried, the lower the control efficiency of the isolation pile on surface settlement. In this study, the control efficiency of isolation piles on the settlement of deep soil mass is basically negative, indicating that the placement of isolation piles increases the original settlement of deep soil mass, instead, resulting in negative effects. The research can provide a reference for the design and construction of isolation pile.